5d Conformal matter - Mario De Marco; Michele Del Zotto; Michele Graffeo; Andrea Sangiovanni (Journal of High Energy Physics)
Abstract Six-dimensional superconformal field theories (SCFTs) have an atomic classification in terms of elementary building blocks, conformal systems that generalize matter and can be fused together to form all known 6d SCFTs in terms of generalized 6d quivers. It is therefore natural to ask whether 5d SCFTs can be organized in a similar manner, as the outcome of fusions of certain elementary building blocks, which we call 5d conformal matter theories. In this project we begin exploring this idea and we give a systematic construction of 5d generalized “bifundamental” SCFTs, building from geometric engineering techniques in M-theory. In particular, we find several examples of ( e 6 $$ {\mathfrak{e}}_6 $$ , e 6 $$ {\mathfrak{e}}_6 $$ ), ( e 7 $$ {\mathfrak{e}}_7 $$ , e 7 $$ {\mathfrak{e}}_7 $$ ) and ( e 8 $$ {\mathfrak{e}}_8 $$ , e 8 $$ {\mathfrak{e}}_8 $$ ) 5d bifundamental SCFTs beyond the ones arising from (elementary) KK reductions of the 6d conformal matter theories. We show that these can be fused together giving rise to 5d SCFTs captured by 5d generalized linear quivers with exceptional gauge groups as nodes, and links given by 5d conformal matter. As a first application of these models we uncover a large class of novel 5d dualites, that generalize the well-known fiber/base dualities outside the toric realm.